A revisionist study of Intellectual Capital disclosure in the international context - Ensslin, Sandra Rolim; De Carvalho, Fernando Nitz (Anais do Congresso Brasileiro de Custos - ABC)
This article presents a revisionist study of Intellectual Capital (IC) disclosure in the international context by means of an analysis of the state-of-the-art in the publications of two specialized and established journals during the period of 2000 and 2005. Its main objective is to look at researchers' procedures to chart the forms of IC disclosure in international organizations. Relevance of the study can be claimed in terms of the organization and systematization of such procedures with a view to providing both the scientific community and the organizations concerned with disclosing their IC - both internally and externally - with a fruitful methodological framework. To this end, a summary of typical procedures is presented initially - accompanied by critical comments - including data collection sources and the procedures used by researchers to identify IC disclosure in terms of method and rationale informing the clustering process. Then the results obtained are discussed in terms of (i) the most representative IC category; (ii) the nature of the disclosure; and, finally, (iii) the uses made of IC information. A tendency towards replication of studies based on the 'content analysis' technique adapted by Guthrie et al (1999) to the investigation of IC disclosure.